Pengaruh Pembelajaran Akidah Akhlak terhadap Karakter Religius Siswa Kelas VII di MTs Tahfidzul Qur'an Darul Falah Al Fatahiyah - Zakiyal Zam Zami; Moch. Noer Azis; Alica Nur Oktavia; Rifa Sindi Olivia; Nudia Amburika (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
The formation of religious character is a central goal of Islamic education, and the Akidah Akhlak subject serves as one of its main vehicles, shaping students who hold firm belief, practice piety, and display good moral conduct. This study examines the extent to which Akidah Akhlak instruction affects the religious character of seventh-grade students at MTs Tahfidzul Qur'an Darul Falah Al Fatahiyah in Palang District, Tuban Regency, a madrasah operating within a pesantren environment. A quantitative, associative design was applied, involving the entire population of 28 seventh-grade students as the research sample through a saturated sampling technique. Data were gathered using Likert-scale questionnaires supported by observation and documentation, then processed through simple linear regression and a t-test in SPSS after the instrument passed validity, reliability, and normality checks. The analysis produced a calculated t-value of 5.284 against a table value of 2.056 at a significance level of 0.000 (p < 0.05), confirming that Akidah Akhlak learning exerts a positive and significant effect on students' religious character. The regression coefficient of 0.731 further indicates a direct relationship between the two variables, while the coefficient of determination (R²) shows that this learning process accounts for 51.8% of the variation in religious character, with the remaining portion shaped by other factors such as family environment and peer influence. The study concludes that strengthening the quality of Akidah Akhlak instruction, supported by teacher exemplary conduct and a consistent religious school culture, remains a strategic pathway for cultivating religious character among students in pesantren-based madrasahs.